ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI INTEGRITAS LAPORAN KEUANGAN (Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI periode Tahun 2014-2017) - Suciani - Primawati; Suprantiningrum Suprantiningrum (Serat Acitya, 2018)
The purpose of this study was to determine the effect of institutional ownership, managerial ownership, firm size, leverage, audit quality and independent board of commissioners on the integrity of financial statements on property and real estate companies listed on the IDX for the 2014-2017 period.The population in this study are 28 property and real estate developers registered in BEI during 2014-2017. By using saturated sampling method or census so the data analysis of financial statements from 28 companies for 4 years, the writer obtains 112 samples of observation data. The data analysis test uses classical assumption test followed by multiple linear regression test. The results of the study indicate that: institutional ownership has a positive effect on the integrity of the company's financial statements. Managerial ownership does not affect the integrity of the company's financial statements. Company size does not affect the integrity of financial statements. Financial leverage has a negative effect on the integrity of financial statements. Audit quality does not affect the integrity of financial statements. The Independent Board of Commissioners has a positive effect on the integrity of the Company's financial statements.Keywords: institutional ownership, managerial ownership, company size, leverage, audit quality, independent board of commissioners and integrity of financial statements